1999
DOI: 10.1046/j.1365-2141.1999.01129.x
|View full text |Cite
|
Sign up to set email alerts
|

The difference in NK‐cell activity between patients with non‐Hodgkin's lymphomas and Hodgkin's disease

Abstract: Summary. Natural killer (NK) cells play an important role in immune surveillance against malignant diseases. Considering the lymphoid origin of malignant lymphomas, as well as scarce data concerning NK-cell function in these neoplasms, we evaluated NK-cell activity in 49 patients with nonHodgkin's lymphomas (NHL) and 47 patients with Hodgkin's disease (HD), prior to therapy. Using the recommended International Working Formulation and the Ann Arbor staging system for classification of lymphomas we found, by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 59 publications
0
57
0
Order By: Relevance
“…Given the documented role of the NKG2D/NKG2DL system for immune surveillance (21,(38)(39)(40)) the induction of NKG2D ligands could have a profound effect on the antitumor response and may counteract the inhibitory effects of HSP90 inhibition on other immune cells. Although Hodgkin's lymphoma cells frequently down-regulate surface expression of MHC-I and should therefore be susceptible to NK cell-mediated immunity, deficiencies in number and function of NK cells have been observed in the blood of Hodgkin's lymphoma patients and in Hodgkin's lymphoma tumors (41)(42)(43)(44). In accordance, a recent familial genotyping study revealed that individuals with certain alleles of activating KIR NK cell receptors were less likely to develop Hodgkin's lymphoma (45), further strengthening that Hodgkin's lymphoma patients might benefit from therapies that support NK cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…Given the documented role of the NKG2D/NKG2DL system for immune surveillance (21,(38)(39)(40)) the induction of NKG2D ligands could have a profound effect on the antitumor response and may counteract the inhibitory effects of HSP90 inhibition on other immune cells. Although Hodgkin's lymphoma cells frequently down-regulate surface expression of MHC-I and should therefore be susceptible to NK cell-mediated immunity, deficiencies in number and function of NK cells have been observed in the blood of Hodgkin's lymphoma patients and in Hodgkin's lymphoma tumors (41)(42)(43)(44). In accordance, a recent familial genotyping study revealed that individuals with certain alleles of activating KIR NK cell receptors were less likely to develop Hodgkin's lymphoma (45), further strengthening that Hodgkin's lymphoma patients might benefit from therapies that support NK cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…This KIR-mediated recognition of missing self is the basis for donor-versus-recipient NK cell alloreactivity in KIR ligand-mismatched hematopoietic transplants in adult AML, which is extensively being investigated and reviewed by others. [6][7][8][9] Although also endogenous NK cells can target cancer cells and have been proven useful for cancer immunotherapy, 10,11 several hematological malignancies, [12][13][14] including AML, encompass significant impaired NK cell functions contributing to the escape of immune surveillance. In this review, we will discuss these mechanisms in AML, as well as strategies to restore NK-cellmediated anti-leukemia responses.…”
Section: Natural Killer (Nk) Cells T Cells and Dendritic Cells (Dc)mentioning
confidence: 99%
“…A myriad of reports rapidly followed, supporting the involvement and therapeutic potential of NK cells in cancer immunity [3,4]. A range of solid tumors [5][6][7][8][9][10][11][12] and hematological malignancies [13][14][15][16][17][18][19] were shown to be associated with significantly impaired NK cell functions. Importantly, NK cell abnormalities have been shown to be, at least in part, responsible for the failure of antitumor immunity.…”
Section: Natural Killer Cells In Cancermentioning
confidence: 99%